Efficacy and safety of up to 192 weeks of etanercept therapy in patients with ankylosing spondylitis. Issue 3 (29th October 2007) - Davis, J C; van der Heijde, D M; Braun, J; Dougados, M; Clegg, D O; Kivitz, A J; Fleischmann, R M; Inman, R D; Ni, L; Lin, S-L; Tsuji, W H
Abstract : Objective: Evaluate long-term safety and efficacy of etanercept treatment in patients with ankylosing spondylitis (AS). Methods: Patients with AS who previously participated in a randomised controlled trial (RCT) of etanercept were eligible to enrol in a 168-week open-label extension (OLE). Safety end points included rates of adverse events (AE), serious adverse events (SAE), infections, serious infections and death. Efficacy end points included Assessment in Ankylosing Spondylitis (ASAS20) response, ASAS 5/6 response and partial remission rates. Results: A total of 257 of 277 patients (92%) enrolled in the OLE. After up to 192 weeks of treatment with etanercept, the most common AEs were injection site reactions, headaches and diarrhoea. The exposure-adjusted rate of SAEs was 0.08 per patient-year. The rate of infections was 1.1 per patient-year, and the rate for serious infections was 0.02 per patient-year. No deaths were reported. Of patients who received etanercept in both the RCT and OLE and were still in the trial, 71% were ASAS20 responders at week 96, and 81% were responders at week 192. ASAS 5/6 response rates were 61% at week 96 and 60% at week 144, and partial remission response rates were 41% at week 96 and 44% at week 192. Placebo patients who switched to etanercept in the OLE showed similar patterns of efficacy maintenance. Conclusions: Etanercept was well tolerated for up to 192 weeks in patients with AS, with no unexpected AEs or SAEs observed. No deaths were reported. Improvements in the signs and symptoms of AS were maintained for up to 192 weeks.